The Cold Light of Dawn : A History of Canadian Astronomy - Jarrell, Richard A. (Book collections on Project MUSE., 1988)
The discovery in 1987 of a supernova brought to world attention the excellence of Canadian astronomers. As Richard Jarrell explains in this book, the path to excellence has been a long one. Its professional status has slowly evolved in much the same way as has the nation itself.